1988
DOI: 10.1002/jbm.820220105
|View full text |Cite
|
Sign up to set email alerts
|

AES analysis of stainless steel corroded in saline, in serum and in vivo

Abstract: Auger electron spectroscopic (AES) studies were conducted to examine the surface film of stainless steel specimens which had been subjected to passive and anodic corrosion in vitro and in vivo. Anodic corrosion was accelerated by the application of a +500 mV (SCE) potential for 30 minutes. Experiments performed in 0.9% saline indicated little alteration in the nature of the surface film compared to a freshly prepared control specimen. Auger analysis of specimens in 10% serum or in vivo revealed that passive fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 11 publications
0
20
0
1
Order By: Relevance
“…Roscoe et al [1] claimed that the increased metal dissolution of stainless steel was due to the adsorption of BSA onto the surface, evidenced from electrochemical impedance study. Other works using Auger electron spectroscopy (AES) revealed that thicker films (carbon-rich) formed on stainless steels that were immersed in 10% serum than in 0.9% saline [8,9]. The carbon layer was also present when the stainless steel was anodically polarised at 500 mV (standard calomel electrode), and the concentration and film thickness increased with the polarising time.…”
Section: Discussionmentioning
confidence: 97%
“…Roscoe et al [1] claimed that the increased metal dissolution of stainless steel was due to the adsorption of BSA onto the surface, evidenced from electrochemical impedance study. Other works using Auger electron spectroscopy (AES) revealed that thicker films (carbon-rich) formed on stainless steels that were immersed in 10% serum than in 0.9% saline [8,9]. The carbon layer was also present when the stainless steel was anodically polarised at 500 mV (standard calomel electrode), and the concentration and film thickness increased with the polarising time.…”
Section: Discussionmentioning
confidence: 97%
“…Thus BSA could build a pellicle layer which can serve as a diffusion barrier for ionic components and reduce susceptibility to pitting attack. In vitro, proteins have been reported to increase corrosion for SS and pure metals 21,22. Metal-protein surface complex exposure to human plasma fibronectin built by Endo could reduce the corrosion rate of Nitinol.…”
Section: Resultsmentioning
confidence: 99%
“…Past research supports the concept that biological molecules such as proteins and microbes also alter corrosion of the alloy 6, 11–21. Separately, static loading stresses and electrolytes with added proteins have been found to reduce the corrosion resistance of implants 6, 21–23.…”
Section: Introductionmentioning
confidence: 93%